HCf-6, a novel class II hydrophobin from Cladosporium fulvum - Nielsen, P.S.; Clark, A.J.; Oliver, R.P.; Huber, M.; Spanu, P.D.
C. fulvum, a fungal tomato pathogen, has previously been shown to express a complex family of hydrophobin genes including four class I hydrophobins and one class II hydrophobin. Here we describe a gene for HCf-6, a sixth member of the hydrophobin family and the second class II gene. The protein is predicted to consist of a signal sequence, an N-terminus rich in glycine and asparagine and a C-terminal hydrophobic domain which bears the hall-marks of hydrophobins. In contrast to the previously described class II hydrophobin HCf-5, HCf-6 is expressed in mycelium growing in pure culture and mRNA levels do not increase during sporulation. It is downregulated by carbon starvation but not by depletion of nitrogen in the growth medium.
Keywords: HYDROPHOBINS; CLADOSPORIUM FULVUM; SPORULATION; GLYCINE/ASPARAGINE-RICH; TOMATO LEAF MOULD